Scaffolded mobile educational game for learning CPU scheduling / Najah Raihan Mustafar @ Mokhtar - Mustafar @ Mokhtar, Najah Raihan (2017)
One of the main topics in Operating System course is CPU scheduling which is often considered difficult by Computer Science and Information Technology students to learn and visualize. This is because student found that learning traditionally is boring and nonengaging. Hence, an alternative to design a scaffolded mobile educational game is carried out to solve these problems. In addition, a few scaffolding characteristics are identified to be adapted in this mobile educational game to enhance student engagement. This project focuses on ADDIE model which acquire five phases; Analysis, Design, Development, Implementation and Evaluation. This method approach is systematic and generic for developing learning tools. A total of 20 Computer Science students evaluated the usability and effectiveness of this game prototype. A set of survey questionnaires was given to the students to collect feedback. The results from the survey show that 95% of the 20 students strongly agreed that scaffolding components applied in this mobile educational game prototype which are instruction and hint assist them in understanding CPU scheduling concept while 75% of the respondents positively agreed that this educational game prototype provides easier learning. Thus, students will be more engages and improve their learning in CPU scheduling from this scaffolded mobile educational game.